Family deviation as a criminological problem - Ларченко, Марина Олександрівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2011)
The author concludes that alcohol abuse, poor  living conditions and a significant difference of social roles and  status, disruption of  family structure and management  practices,  lack of  social-psychological communication spouses, are factors of the criminalization of family relations.